Degree of Applying Quality Standards in the Program of Preparing Special Education Teachers at the University of Princess Noura bint Abdurrahman in the Kingdom of Saudi Arabia from the Female Students' Perspective:A comparative Study between 2014 and 2017 - Hanadi A Qadan (University of Science and Technology, Yemen, 2017)
This study aimed to find out the degree of applying the quality standards within the program of preparing special education teachers at the University of Princess Noura bint Abdurrahman in the Kingdom of Saudi Arabia in the year 2017 compared to 2014. The study sample consisted of (108) students from eighth level, at the Faculty of Education - special education program in 2017. This sample was compared with a sample of (63) students with whom the research tool was used in 2014. To collect the data, a questionnaire consisting of (59) items was developed and classified into six themes: program objectives, curriculum, and methods of teaching, evaluation, facilities, equipment, and field training. The statistical analysis showed that the degree of applying quality standards in the program of preparing teachers of special education at the University of Princess Noura bint Abdurrahman in 2017 was generally rated as high. There were no statistical differences according to the variable of cumulative average. Also, the results revealed statistically significant differences in the degree of applying quality standards in the program of preparing teachers of special education at the University of Princess Noura Bint Abdurrahman in the period 2014-2017 in favor of 2017. It was recommended that total quality standards should be applied so as to achieve the target efficiency which aims to reach the specific objectives in the strategic plan of the university, faculty and department, and to ultimately achieve the national academic accreditation. It was also recommended to keep practicing standards of quality in order to achieve global standards. Keywords: Quality standards, Special education, Teacher education program, Princess Noura Bint Abdurrahman University, Female students, Comparative study.